ANALISIS BERPIKIR KREATIF SISWA SMK DALAM MEMECAHKAN MASALAH MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Dian Lestari; Zubaidah Rasiman; Silvia Sayu (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe purpose of this research is to know and to description creative thinking students of XI in order to solve the problem in material linear equation system of two variables at SMK Negeri 3 Pontianak. This research is focus on how the students creative thinking in ability of high mathematics and students’ ability of low mathematics according to indicator fluency, fleksibility and orginality. This research used descriptive method with qualitative approach. The research is about case study. The tools of data collection in the form of test descriptions and unstructured interviews. As for the subject of this study were students of class XI Office Administration 2 SMK Negeri 3 Pontianak. The results showed that the average students met the fluency indicator and on average reached a creative thinking level 1 (less creative). The average students with high mathematical ability reaches a creative thinking level of 1 (less creative) and the average students with low math ability reaches a creative thinking level of 0 (not creative). Therefore, it can be concluded that students of XI have not been creative in solving linear equation system of two variables.Keywords: Analysis, Mathematical Creative Thinking, Problem Solving